Vascular compliance and left ventricular compliance cross talk: Implications for using long-term heat acclimation in cardiac care - Horowitz, Michal; Hasin, Yonathan (Frontiers in Physiology, 2023)
1) The first evidence of the beneficial impact of Long-Term-Heat-Acclimation (LTHA) on cardio-vascular compliance was the positive inotropic response and improved left ventricular (LV) compliance noted when isolated hearts from LTHA rats were studied. Human echo study demonstrates that passive HA affects the right ventricle and the atria as well. 2) There is a cross-talk between vascular and cardiac compliance. Vascular compliance per se is defined by central venous pressure—Blood volume relationship—Global Vascular Compliance (GVC). It is determined by the sum of the vascular compliance of the vessels in every organ in any physiological state, varies with LTHA and thus influences cardiac performance. LTHA improves endothelial function, increases NO (nitric oxide) production, in-turn stimulating alterations in ECM (extracellular matrix) via the TGF β1-SMAD pathway. 3) LTHA is associated with transformation from fast to slow myosin, heat acclimation ischemic/hypoxic cross-tolerance and alterations in the extracellular matrix. 4) A human translational study demonstrated improved LV compliance following bypass surgery in LTHA subjects compared to controls. 5) Diastolic dysfunction and the impact of comorbidities with vascular and non- vascular origins are major contributors to the syndrome of heart failure with preserved ejection function (HFPEF). Unfortunately, there is a paucity of treatment modalities that improve diastolic dysfunction. 6) In the current mini-review we suggest that LTHA may be beneficial to HFPEF patients by remodeling cardiac compliance and vascular response.